2019
DOI: 10.1128/mbio.00713-19
|View full text |Cite
|
Sign up to set email alerts
|

A Substrate-Activated Efflux Pump, DesABC, Confers Zeamine Resistance to Dickeya zeae

Abstract: Zeamines are a family of polyamino phytotoxins produced by Dickeya zeae EC1. These phytotoxins are also potent antibiotics against a range of microorganisms. To understand how D. zeae EC1 can protect itself from the antimicrobial activity of zeamines, we tested whether the ABC transporter genes within the zms (zeamine synthesis) gene cluster were related to zeamine resistance. Our results ruled out the possible involvement of these ABC transporters in zeamine resistance and instead unveiled an RND (resistance-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(51 citation statements)
references
References 45 publications
(83 reference statements)
0
51
0
Order By: Relevance
“…The proportion of ABC transporters in the two groups of diseased samples was higher than that in the corresponding two groups of healthy samples, which may be associated with the disease resistance of P. notoginseng . Previous studies have reported that gene modulating resistance helps plants to inhibit pathogenic bacteria and improve plant resistance ( Gong et al, 2020 ; Liang Y. et al, 2020 ; Wang J. et al, 2020 ; Corredor-Moreno et al, 2021 ; Zia et al, 2021 ), while the RND antibiotic efflux mechanism has an efflux effect on various antibiotics; inhibiting these pumps can mitigate antibiotic resistance ( Siriyong et al, 2017 ; Liang et al, 2019 ; Ichinose et al, 2020 ). Our study showed that the RND antibiotic efflux mechanism in diseased samples was greater than that in healthy samples.…”
Section: Discussionmentioning
confidence: 99%
“…The proportion of ABC transporters in the two groups of diseased samples was higher than that in the corresponding two groups of healthy samples, which may be associated with the disease resistance of P. notoginseng . Previous studies have reported that gene modulating resistance helps plants to inhibit pathogenic bacteria and improve plant resistance ( Gong et al, 2020 ; Liang Y. et al, 2020 ; Wang J. et al, 2020 ; Corredor-Moreno et al, 2021 ; Zia et al, 2021 ), while the RND antibiotic efflux mechanism has an efflux effect on various antibiotics; inhibiting these pumps can mitigate antibiotic resistance ( Siriyong et al, 2017 ; Liang et al, 2019 ; Ichinose et al, 2020 ). Our study showed that the RND antibiotic efflux mechanism in diseased samples was greater than that in healthy samples.…”
Section: Discussionmentioning
confidence: 99%
“…The RND superfamily is common in Gram-negative bacteria and is a major contributor to multidrug resistance among human pathogens such as Enterococcus faecium , Staphylococcus aureus , Klebsiella pneumoniae , Acinetobacter baumannii , P. aeruginosa , and Enterobacter species ( Li and Nikaido, 2004 , 2009 ). Moreover, RND efflux pumps have also been reported in plant pathogens, for example, Erwinia amylovora ( Pletzer and Weingart, 2014 ), Dickeya species ( Liang et al, 2019 ), and Pseudomonas syringae ( Stoitsova et al, 2008 ). Research into the RND efflux pump in biocontrol bacteria has been limited.…”
Section: Discussionmentioning
confidence: 99%
“…We also observed a slight inhibition exerted by D. solani D s0432-1 against E. coli , but no inhibition towards D. dadantii and P. atrosepticum . Zeamine resistance of D. dadantii could be explained by the presence in its genome of the genes desAB encoding the RDN pump DesAB involved in zeamine efflux (Liang et al ., 2019). In-frame deletion of desA or desB in D. oryzae EC1 leads to a zeamine sensitive phenotype (Liang et al ., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Zeamine resistance of D. dadantii could be explained by the presence in its genome of the genes desAB encoding the RDN pump DesAB involved in zeamine efflux (Liang et al ., 2019). In-frame deletion of desA or desB in D. oryzae EC1 leads to a zeamine sensitive phenotype (Liang et al ., 2019). In in planta Tn-seq experiments with D. dadantii 3937 (Royet et al ., 2019), mutants of the genes desA and desB (Dda3937_00787 and Dda3937_00786 respectively) did not display a significant negative or positive variation (Log2 fold-changes −0.09 and +0.44, respectively), suggesting that this RND efflux pump does not play a significant role during D. dadantii plant infection, contrary to the D. dadanti RND efflux pump AcrAB that appeared to be essential for virulence (Royet et al ., 2019).…”
Section: Discussionmentioning
confidence: 99%